The mediating role of affective commitment in the relationship between emotional intelligence and perceived organizational support on turnover intention - Prahiawan, Wawan; Maulana, Naepis; Kambara, Roni (Trigin Publisher, 2024)
Among effective management systems, the importance of human resources is increasing. Human resource management in an organization has become one of the most important functions in a company. This study aims to test and analyse the variables that influence turnover intention with emotional intelligence and perceived organizational support through affective commitment to develop a basic theory and research model. This research uses an associative descriptive quantitative method with a sample of 195 respondents with technical purposive sampling who are PT Luhai Industrial Cikande Serang employees. Questionnaire answers were measured using an interval scale of 1 - 10. The data was analysed with the help of SmartPLS Version 4.0 software. The results showed statistically, emotional intelligence can significantly negatively affect turnover intention, perceived organizational support has no significant effect on turnover intention, emotional intelligence can significantly positively affect affective commitment, perceived organizational support can significantly positively affect affective commitment, affective commitment can significantly negatively affect turnover intention, affective commitment can mediate the effect of emotional intelligence on the turnover intention with partial mediation characteristics while affective commitment can mediate the effect of perceived organizational support on the turnover intention with full mediation characteristics